Influence of viscosity and ionic concentration on morphology of PLZT thin films - Simoes, A. Z.; Gonzalez, AHM; Zaghete, M. A.; Cilense, M.; Varela, José Arana [UNESP]; Stojanovic, B. D. (Elsevier B.V., 2001)
PLZT thin films were prepared by a dip-coating process using Pechini's method. The PLZT solution was obtained from the mixture of the cation solutions. The viscosity of the solution was adjusted in the range of 20-40 cP, while the ionic concentration was adjusted in the range of 0.1 and 0.2 M. PLZT solutions were deposited on Si (1 0 0) substrate with withdrawal speed at 5 mm/min. The coated substrates were thermally treated with heating rate of 1 degreesC/min up to 300 and 5 degreesC/ min up to 650 degreesC in order to obtain homogeneous and crack free films. The influence of viscosity and ionic concentration on crystallization and morphology of PLZT (9/65/35) thin film will be discussed. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: PLZT; annealing; crystallization; X-ray diffraction; electron microscopy